Potential benefits to breeding seabirds of converting abandoned coconut plantations to native habitats after invasive predator eradication. Issue 5 (4th July 2021) - Carr, Peter; Trevail, Alice; Bárrios, Sara; Clubbe, Colin; Freeman, Robin; Koldewey, Heather J.; Votier, Stephen C.; Wilkinson, Tim; Nicoll, Malcolm A. C.
Abstract : On many Pacific and Indian Ocean islands, colonization by humans brought invasive species, native vegetation destruction, and coconut plantations, leading to the decimation of seabird populations. The coconut industry on oceanic islands has since crashed, leaving the legacy of altered, impoverished ecosystems. Many island restoration projects eradicate invasive species, particularly rats, with the goal of restoring seabird‐driven ecosystems. However, in the absence of converting abandoned plantations to habitat conducive to breeding seabirds, seabird‐driven ecosystems may not fully recover after rat eradication. Here we quantify and, by resource selection function, confirm seabird habitat selection within the Chagos Archipelago, before estimating the potential difference in breeding abundance following rat eradication with and without active management of abandoned plantations. Using Ile du Coin as our primary example, we estimate that following rat eradication, but without plantation conversion, this island could potentially support 4, 306 (±93) pairs of breeding seabird; if restored to habitat representative of associated rat‐free islands, 138, 878 (±1, 299) pairs. If 1 km 2 of plantation is converted to produce 0.5 km 2 each of native forest and savanna, it could theoretically support 319, 762 (±2, 279) breeding pairs—more than the entire archipelago at present. Our research indicates that when setting restoration goals in the Chagos Archipelago, at least 55% of the restored habitat should be composed of native forest and savanna in order to support a viable seabird community. Our research enhances the prospects of successfully restoring seabird islands across the tropical landscape with wider benefits to native biodiversity.